Determination of urban sprawl on ecological network using edge analysis: a case study of Usak (Turkey) - Kocan, Nurhan (Journal of Environmental Engineering and Landscape Management, 2021)
The aim of this study is to investigate the effects of the urban development of Usak city onto natural and urban open green spaces around the city during a -fifty- year period between 1954–2004. The data is based on aerial photographs of Usak urban area in 1954, 1971, 1994 and from Ikonos satellite image of 2004. The statistical data and the visual maps created in geographic information system software. This study puts forward the rapid spread of urbanization from 1971 to 1994 and hence, a significant change in landscape mosaic; urban areas increased by 102.9% between 1954–1971, 226.1% between 1971–1994 and 99.3% between 1994–2004. The most crucial change is evident in agricultural and open areas. According to the results of the edge analysis, urban areas, border ecologically valuable natural areas and the highest rate value was found to be in 2004; proving the development of the city towards agricultural areas.